Drying kinetics and properties evolution of apple slices under convective and intermittent-MW drying. (1st May 2022) - Joardder, Mohammad U.H.; Karim, M.A.
Highlights: Intermittent Microwave Convective Drying (IMCD) removes water faster. Case hardening in the IMCD treated food samples was significantly lower. IMCD deried samples is found softer than convectively dried samples. IMCD treated samples were more appealing compared to convection dried sample. Abstract: Intermittent microwave-convective drying (IMCD) is a relatively advanced drying technology that is used to overcome the shortcomings of microwave, convective, and microwave-convective drying. No research has been done on the evolution of mechanical properties during IMCD of apple. This research aims to shed new light on the effect of heating patterns on the evolution of the mechanical properties of the apple slice. In this research, comparisons of drying and rehydration kinetics of conventional drying IMCD derived samples have also been carried out in light of their mechanical properties changes. The result shows significant differences in drying and rehydration kinetics between IMCD dried and convective dried food materials. To remove the same amount of moisture, convective heating takes about 10 times more time compared with IMCD. Moreover, better rehydration capacity and appearance have been found in IMCD dried samples. Eventually, IMCD offers an energy-efficient quick drying option along with retaining higher quality than conventional drying.